Executive Character and Tax Behavior in Property and Real Estate Sector: An Empirical Study: Karakter Eksekutif, Intensitas Modal, dan Perilaku Perpajakan dalam Sektor Properti dan Real Estat: Analisis Empiris - Evinka Wijayanti; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2022)
This study investigates the relationship between executive character, capital intensity, and tax behavior in property and real estate service companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2019. The research aims to examine the impact of executive character and capital intensity on both tax avoidance and tax aggressiveness within the sector. Purposive sampling was employed, resulting in a sample size of 15 IDX-listed property and real estate service companies. Multiple linear regression analysis was conducted using the SPSS program. The findings reveal that executive character significantly influences tax avoidance in the IDX property sector, while capital intensity also has a significant effect on tax avoidance in this sector. Furthermore, executive character significantly impacts tax aggressiveness in the IDX property sector. However, capital intensity was found to have no effect on tax aggressiveness in the same sector. These results provide valuable insights for researchers, practitioners, and policymakers by highlighting the role of executive character and capital intensity in shaping tax behavior within the property and real estate industry. Highlights: The study examines the influence of executive character and capital intensity on tax behavior in the property and real estate sector. Findings show that executive character significantly affects tax avoidance and tax aggressiveness in the sector. Capital intensity has a significant impact on tax avoidance, but not on tax aggressiveness, within the property and real estate industry. Keywords: Executive character, Capital intensity, Tax behavior, Property sector, Real estate sector.